Kebijakan Dividen: Strategi Perusahaan dalam Bayang-Bayang Struktur Kepemilikan - Purbaningsih, Restu Aurelia; Sari, Shinta Permata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The dividend policy is a company's decision regarding whether the profits earned will be distributed to investors as dividends or retained as retained earnings. This study aims to analyze the influence of ownership structure, such as Managerial Ownership, Institutional Ownership, Public Ownership, and Foreign Ownership on Dividend Policy. The sample in this study includes all energy sector companies listed on the Indonesia Stock Exchange from 2020 to 2024. The sampling technique used is purposive sampling, resulting 16 energy companies that meet the research criteria. The research method employed is quantitative research. The data source is secondary data, specifically the companies' annual reports. The analysis technique used is multiple linear regression analysis with SPSS 27. Dividend Policy is measured by the Dividend Payout Ratio. The results show that Institutional Ownership and Foreign Ownership have effect on Dividend Policy, while Managerial Ownership and Public Ownership have no effect on Dividend Policy.